Coercivity enhancement of Ce-Fe-B sintered magnets by low-melting point intergranular additive - 陈侃 郭帅 范晓东 丁广飞 陈岭 陈仁杰 李东 闫阿儒 (Journal of rare earths, 2017)
Ce-Fe-B sintered magnets with enhanced coercivity were prepared by the powder metallurgy method. The mechanism of the coercivity enhancement in Ce-Fe-B sintered magnets with the low-melting point intergranular additive was discussed in details. It was speculated that the low coercivity of Ce-Fe-B sintered magnet was related to the irregular sharps and relatively low magneto-anisotropy field of the matrix phase. After introducing a 20 wt.% Nd-based intergranular additive, the coercivity markedly increased from 108 Oe to 2560 Oe due to the formation of thin and continuous grain boundary layers and the surface modification of the matrix phase grains. Additionally, the formation of the high anisotropy field（Nd,Ce）_2Fe_（14）B shell was beneficial to the increase of the coercivity as well. This work suggested that adding low-melting point intergranular additives was effective to fabricate the practical Ce-Fe-B sintered magnets.